Treinamento e capacitação dos profissionais da construção civil baseados nos conceitos da mentalidade enxuta - Panaino, Brunna Bernardo de Faria (2015)
The industry of civil construction presents frequent progress in material development, but a notable delay in management. To assist in the management process, it has been sought to adopt the concept of lean thinking that emerged in the automotive industry and it has been adapted to various segments because of its efficiency. They have developed several theoretical works on the subject, but there are still difficulties in the implementation in construction due to low education of the workforce; lack of organizational diagnosis, among others. This work aims to present a form of training for the workforce with a focus on reducing waste and loss based on the concepts of lean thinking. Classified as action research, the following steps were included: (1) literature review on teaching methods, training and lean thinking; (2) development of preliminary proposal of training and capacity and its evaluation mechanisms and subsequent (3) application and validation (4) final proposal for the training and qualification method. The application shows that the model developed contributes to filling thegap between the lean construction theory and the practice of construction. The uniqueness of the model consists of the application of the training with pedagogical foundations of learning styles to best suit the target audience.